Neonatal skin care. A four-week follow up randomized controlled trial. - Amer, M.; Amer, A. (European Journal of Pediatric Dermatology, 2015)
The major functions of the human skin are maintenance of water and electrolyte homeostasis, thermoregulation, antimicrobial defense, protection from trauma, environmental toxins and ultraviolet radiation, synthesis of vitamin, immune surveillance; it is important from an esthetic point of view, serves as a sensory organ and facilitates mother-child attachment. The skin of the newborn differs from that of an adult in several ways. Newborn skin care is mandatory to avoid skin infections. As a result of normal daily exposure to these external factors, good skin hygiene, proper skin cleansing and protection of the infant skin barrier are essential to maintain the barrier function and overall health. The aim of this work is to assess the neonatal skin care effectiveness in promotion of normal skin development and protection of the optimal skin function to prevent the different neonatal skin disorders.